Establishing and Maintaining a Personal Leadership Network - Jared Rawlings; Christopher Jochum (Academic Chairpersons Conference Proceedings, 2023)
In this session, two academic leaders will share lessons learned during their first years leading a department. This session will include advice related to establishing and maintaining a personal leadership network.
Keywords: Departmental leadership; Servant Leadership; Leadership Network; Time management